Application of uniform design to evaluate the diferent conditions on the growth of algae Prymnesium parvum - JuanYin; Xuyang Sun; Ruizhi Zhao; Xiaocong Qiu; Eeswaran, R. (Scientifc Reports, 2021)
Prymnesium parvum is an environmentally harmful algae and well known for its toxic efects to the fsh culture. However, there is a dearth of studies on the growth behavior of P. parvum and information on how the availability of nutrients and environmental factors afect their growth rate. To address this knowledge gap, we used a uniform design approach to quantify the efects of major nutrients (N, P, Si and Fe) and environmental factors (water temperature, pH and salinity) on the biomass density of P. parvum. We also generated the growth model for P. parvum as afected by each of these nutrients and environmental factors to estimate optimum conditions of growth. Results showed that P. parvum can reach its maximum growth rate of 0.789, when the water temperature, pH and salinity is 18.11 °C, 8.39, and 1.23‰, respectively. Moreover, maximum growth rate (0.895–0.896) of P. parvum reached when the concentration of nitrogen, phosphorous, silicon and iron reach 3.41, 1.05, 0.69 and 0.53 mg/l, respectively. The order of the efects of the environmental factors impacting the biomass density of P. parvum was pH> salinity >water temperature, while the order of the efects of nutrients impacting the biomass density of P. parvum was nitrogen>phosphorous > iron> silicon. These fndings may assist to implement control measures of the population of P. parvum where this harmful alga threatens aquaculture industry in the waterbodies such as Ningxia region in China